Evaporation of a free microdroplet of a binary mixture of liquids with different volatilities. Issue 8 (29th January 2019) - Kolwas, Maciej; Jakubczyk, Daniel; Do Duc, Tho; Archer, Justice
Abstract : We observed in experiment and modelled analytically several modes of distillation in free microdroplets of binary mixtures. Abstract : We have investigated fine details of evaporation of free microdroplets of liquid binary mixtures comprising ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TEG), glycerol and water. The microdroplets were kept and studied in an electrodynamic trap. Several phenomena associated with their evaporation are identified, discussed and modelled analytically. In particular, we've observed distillation at the microscale manifesting as a sigmoid transition of the evaporation rate (surface change rate). Sigmoid transition is known to be a characteristic feature for the evolution of the population (amount) with limited resources. We have shown that the transition itself can be comprehended using a stationary evaporation model under instantaneous mixing conditions. The condition is discussed and justified. The more general findings are primarily exemplified by a practical case of DEG contaminated with water by considering a humid and a dry ambient atmosphere. The influence of the composition of the droplet and the ambient atmosphere on the initial (pre-transition) stage of evaporation is considered in a general manner. Three types of conditions are discussed concerning the presence of an admixture in liquid and vapour phases (exemplified by the DEG/water system): (i) "dry" liquid – dry atmosphere, (ii) "wet" liquid – dry atmosphere, and (iii) "wet" liquid – wet atmosphere. Case (i) has been successfully verified against the theoretical prediction. Case (ii) has the requirement of considering non-stationary liquid-in-liquid diffusion. Case (iii) has led to a study of evaporation of a liquid mixture microdroplet with the more volatile component in equilibrium with its vapour.